Mindfulness in the focus of the neurosciences - The contribution of neuroimaging to the understanding of mindfulness - Weder, Bruno J. (Frontiers in Behavioral Neuroscience, 2022)
Background Mindfulness affects human levels of experience by facilitating the immediate and impartial perception of phenomena, including sensory stimulation, emotions, and thoughts. Mindfulness is now a focus of neuroimaging, since technical and methodological developments in magnetic resonance imaging have made it possible to observe subjects performing mindfulness tasks. Objective We set out to describe the association between mental processes and characteristics of mindfulness, including their specific cerebral patterns, as shown in structural and functional neuroimaging studies. Methods We searched the MEDLINE databank of references and abstracts on life sciences and biomedical topics via PubMed using the keywords: “mindfulness”, “focused attention (FA)”, “open monitoring (OM)”, “mind wandering”, “emotional regulation”, “magnetic resonance imaging (MRI)” and “default mode network (DMN)”. This review extracted phenomenological experiences across populations with varying degrees of mindfulness training and correlated these experiences with structural and functional neuroimaging patterns. Our goal was to describe how mindful behaviour was processed by the constituents of the default mode network during specific tasks. Results and Conclusions Depending on the research paradigm employed to explore mindfulness, investigations of function that used fMRI exhibited distinct activation patterns and functional connectivities. Basic to mindfulness is a long-term process of learning to use meditation techniques. Meditators progress from voluntary control of emotions and subjective preferences to emotional regulation and impartial awareness of phenomena. As their ability to monitor perception and behaviour, a metacognitive skill, improves, mindfulness increases self-specifying thoughts governed by the experiential phenomenological self and reduces self-relational thoughts of the narrative self. The degree of mindfulness (ratio of self-specifying to self-relational thoughts) may affect other mental processes, e.g., awareness, working memory, mind wandering and belief formation. Mindfulness prevents habituation and the constant assumptions associated with mindlessness. Self-specifying thinking during mindfulness and self-relational thinking in the narrative self relies on the default mode network. The main constituents of this network are the dorsal and medial prefrontal cortex, and posterior cingulate cortex. These midline structures are antagonistic to self-specifying and self-relational processes, since the predominant process determines their differential involvement. Functional and brain volume changes indicate brain plasticity, mediated by mental training over the long-term.